Europe's Islamic Legacy: 1900 to the Present Proceedings of the Online Conference Hosted by the University of Cambridge on 20 October 2020 - Drayson, Elizabeth (Brill, 2023)
Seven new scholarly essays present original research that includes rare historical and photographic materials highlighting the significance of Islamic civilization and its vexed legacy in a variety of contemporary European countries and challenging the perception of European identity as exclusively Christian. This volume unearths a rich, complex history of relationships between Muslims and Christians in Europe whose value lies in the close and continued connections between them that began so long ago on European soil.